Effect of Competence and Ship Crew Discipline on Performance PT. Myclin Express Offshore - Malau, April Gunawan; Barasa, Larsen; Sumali, Bambang (International Review of Management and Marketing, 2019)
Every shipping company needs competent and qualified ship crews in carrying out activities in order to help the company achieve company performance. In addition to supporting crew competence, another factor which is no less important is the discipline of the crew itself. But in reality many crew members do not meet the standards and qualifications given by the company, so they do not provide maximum performance, as a result the achievement of company performance is very low. Solving problems related to this matter is the holding of job training in the field of Human Resources Management (HRM) with the aim of forming competent crew so that in the future it is expected to provide optimal company performance. Problems regarding discipline crew are the low awareness of the ship's crew of the importance of discipline while working on the ship. The right way to overcome this is to conduct training to increase crew awareness and to conduct periodic evaluations of the implementation of activities that assess the discipline of the crew. The purpose of this study was to determine how much influence the competence and discipline on the performance of P T. Myclin Express Offshore with technical data analysis using multiple regression methods. The independent variable in this study is the competence variable and the disciplinary variable, while the dependent variable is the performance variable PT.Myclin Express Offshore. Keywords: Competence, Compensation, Company Performance. JEL Classifications: L62, R41, R42 DOI: https://doi.org/10.32479/irmm.8530